PENGARUH LINGKUNGAN KERJA SERTA MOTIVASI KERJA TERHADAP KEPUASAN KERJA PT. SKF INDONESIA - Muhammad Richo Rianto; Dela Rosa, Dela (Sekolah Vokasi, Universitas Sebelas Maret, 2023)
Abstrak : Every government organization, whether large or small, needs to become more effective and efficient. The human factor needs to be taken into account in management so that the effect is consistent with what the organization or business expects to achieve its pre-set goals. When a person can discover their potential for work through their work, they continue to work with enthusiasm. Employee job satisfaction is an essential factor in employee well-being, discipline, and performance at work, all of which support company goals. The purpose of this study is to understand the work environment and motivation that are related to employee recruitment practices at PT SKF Indonesia.